Dynamics of Couples in Divorce in Court - Ningsih, Yosi Aprilia; Ningsih, Silvianetri; Rahayu, Sri Putri; Jixiong, Cai (Yayasan Minang Darussalam, 2023)
This research discusses the problems faced by a widow after divorce, including the negative view of their status from society and the changes experienced both personally and in the neighbourhood. The purpose of this study is to understand the cognitive, affective, and conative dynamics experienced by divorced couples. This study used a descriptive qualitative method and involved one husband informant and one wife informant. Data were collected through interviews, then analysed using data reduction, data presentation, and conclusion drawing techniques. The results showed that there were psychological changes in couples who experienced divorce in cognitive, affective, and conative aspects. In the cognitive aspect, changes can be seen from the disharmony of household relationships and the desire for a better life after divorce. Meanwhile, in the affective aspect, there are differences between couples who feel sad and happy in making the decision to divorce. However, the decision to divorce is not easy for them.